Influence of genetic markers on the feeding behavior of yearling bulls - Garza-Brenner, Estela; Sifuentes-Rincón, Ana M.; Rodríguez Almeida, Felipe A.; Randel, Ronald D.; Parra-Bracamonte, G. Manuel; Arellano Vera, Williams (Revista Colombiana de Ciencias Pecuarias, 2019)
Background: The search for gene and marker effects on economically important traits is aimed not only to understanding the genetic architecture of complex traits but also to applying the information to breeding schemes. Objective: To analyze the effect of two temperament-related SNPs (rs109576799 located in the DRD3 gene, and rs43696138 in the HTR2A gene) on feeding performance of Mexican beef cattle. Methods: One hundred and thirty-six young beef bulls were included in a centralized feed efficiency performance test based on residual feed intake (RFI), with 20 d for adaptation and 70 d of feed efficiency testing. In addition to feeding traits, temperament was assessed at the beginning of the trial using pen score (PS) and exit velocity (EV). All animals were genotyped with two markers located in the HTR2A and DRD3 genes, and an association analysis was conducted between these genotypes and the measured traits. Results: For Brangus breed, a significant association was obtained between average daily gain (ADG; p=0.019), and the rs43696138 marker, resulting in higher gains for homozygous genotype GG (1.69 ± 0.04 kg), when compared to the heterozygous genotype GA (1.54 ± 0.04 kg). Conclusion: The previously reported association of these markers with temperament was not confirmed in the evaluated breeds; however, the rs43696138 marker showed an effect on a feeding performance trait. Further studies are needed to determine the effect of this and other markers on both RFI and temperament.